2017
DOI: 10.1042/bsr20160460
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of adhesion formation after knee surgery in a rat model by botulinum toxin A

Abstract: Adhesion of the knee is a major concern after knee surgery, the treatment of which is difficult. Botulinum toxin A (BTX-A) injection is demonstrated as efficient in treating knee adhesion after surgery. However, the treatment outcomes and the mechanism of action are not yet determined. The aim of the present study was to examine the effects and molecular mechanism of a BTX-A treatment in preventing adhesion of the knee. Twenty-four Wistar rats were randomly divided into a BTX-A treatment group and a control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Fibrosis in joint components strongly contributes to progressing arthrogenic contracture in remobilized (Kaneguchi et al 2017, Kaneguchi et al 2018a, Kaneguchi et al 2018b as well as injured joints (Fukui et al 2000, Fukui et al 2001, Gao et al 2017, Li et al 2013a. Further, we observed increased joint capsule thickness and collagen density in the joint capsule following remobilization together with progressing arthrogenic contracture.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Fibrosis in joint components strongly contributes to progressing arthrogenic contracture in remobilized (Kaneguchi et al 2017, Kaneguchi et al 2018a, Kaneguchi et al 2018b as well as injured joints (Fukui et al 2000, Fukui et al 2001, Gao et al 2017, Li et al 2013a. Further, we observed increased joint capsule thickness and collagen density in the joint capsule following remobilization together with progressing arthrogenic contracture.…”
Section: Discussionsupporting
confidence: 54%
“…We previously showed that anti-inflammatory treatment using the steroidal drug dexamethasone can prevent remobilization-induced arthrogenic contracture progression by suppressing joint capsule fibrosis and fibroblast proliferation (Kaneguchi et al 2018b). Other studies using intra-articular adhesion models also reported that administration of anti-inflammatory agents such as celecoxib and botulinum toxin type A attenuates joint contracture and intra-articular adhesion as well as fibroblast proliferation (Baranowski et al 2019, Gao et al 2017, Li et al 2013a. Fibroblasts produce extracellular matrix proteins such as collagens, and thus fibroblast proliferation is an important process in the development of joint fibrosis (Emami et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the existing studies on medical inhibition of the development of joint contracture (Table 2), an improvement of the range of motion could be achieved mostly after intraarticular application of the respective active agents. 16,17,64,[95][96][97][98][99][100][101][102][103][104] Although these results constitute an opportunity for the development of a medical treatment of patients with PTJS, the intraarticular application is unfavorable for a number of reasons: i) it is a painful and invasive procedure for the patient, ii) it bears the risk of septic arthritis, iii) it might damage the articular cartilage by chondrotoxic effects or iv) weaken the capsule and ligaments of the knee. [105][106][107] Based on the rabbit models of PTJS of Hildebrand et al and Nesterenko et al, our group established a rat model of PTJS of the knee joint that included a rupture of the posterior joint capsule, a hemarthrosis, an intraarticular bone damage and a temporary fixation of the joint.…”
Section: Atorvastatin Inferior Capsulementioning
confidence: 99%
“…The extension range of motion (ROM), or the angle between the longitudinal axis of the femur and the tibia, was measured in triplicate using an angulometer with 20 g force for both the right (implanted) and left (native, control) knee [ 32 ]. Data are expressed as the difference in extension ROM between the native and implanted knee from TXA- and ALM-treated animals.…”
Section: Methodsmentioning
confidence: 99%